A reliable physical unclonable function based on differential charging capacitors - Yuan, Hang (2021)
Physical Unclonable Function (PUF) is an emerging security primitive for cryptography applications. However, achieving a very high reliability against the environmental variations remains a main challenge in PUF design and a key barrier for its commercialization. This paper presents a new PUF design based on the charging of a symmetric MOS capacitor pair by constant current with cross-coupled positive feedback inverters. The proposed weak PUF features high raw response reliability against variations in power supply and temperature without power-up reset noise and other issues due to the power-down and up of an array of cells. Extensive Monte-Carlo simulations have been performed using a standard 110nm CMOS process technology. The simulated results show an almost ideal uniqueness of 50.03% and superior reliability of 97.70% over a temperature range from 0 ̊C to 80 ̊C, and 96.20% with the supply voltage varies from 1.2 V to 1.8 V. The response bit can be generated at a rate of 27.78 Mbps with an average power consumption of 20.86 μW at 1.5V, and the energy consumption is only 750 fJ/bit.